2001
DOI: 10.1046/j.1365-2109.2001.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of variable feed allowance with constant energy and ratio of energy to protein in a diet for constant protein input on the growth of common carp Cyprinus carpio L.

Abstract: An 11‐week feeding trial was conducted to evaluate the effects of dietary protein and/or energy levels on growth, feed efficiency and proximate composition of juvenile (average weight: 21.5 g) common carp (Cyprinus carpio L.) fed various diets based on constant daily protein input. Five experimental diets were prepared. One group of diets (diets 1, 2 and 3) contained three crude protein (P) levels (35%, 40% and 45%) with a constant gross energy (GE) of 3.8 kcal g−1 diet. The second group of diets (diets 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 26 publications
3
14
0
1
Order By: Relevance
“…Além disso, como o arraçoamento foi restrito para todos os tratamentos (3% da biomassa), isto impediu o "consumo compensatório" pelos animais que recebiam as menores concentrações proteicas. Quando os peixes são alimentados com ração restrita, eles crescem mais rapidamente com dietas com alto nível proteico, e quando alimentados até a saciedade, eles respondem melhor aos níveis mais baixos de proteína (Cho et al, 2001).…”
Section: Resultsunclassified
“…Além disso, como o arraçoamento foi restrito para todos os tratamentos (3% da biomassa), isto impediu o "consumo compensatório" pelos animais que recebiam as menores concentrações proteicas. Quando os peixes são alimentados com ração restrita, eles crescem mais rapidamente com dietas com alto nível proteico, e quando alimentados até a saciedade, eles respondem melhor aos níveis mais baixos de proteína (Cho et al, 2001).…”
Section: Resultsunclassified
“…In the present study fish fed diet 2 with low intake of protein in terms of per unit body weight resulted in the highest ANPU and energy retention. It is generally observed in fish that protein retention efficiency increases with low protein intake [19], so less of the dietary protein is either excreted or used as energy substrate. High dietary lipid level in diet 4 (22.7%) did not improve protein retention indicating that no protein sparing effect occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to Keshavanath et al (2002), carp growth in low protein diets compared to high protein diets was not significantly affected, which is in line with the results obtained in the present study. Cho et al (2001) noted that weight gain of common carp decreased linearly with increasing protein level in feed. In the trial conducted by Satpathy et al (2003) the same growth parameters were observed in Indian carp (Cyprinus catla) fed diets contained 35% or 40% of crude protein.…”
Section: Production Performancementioning
confidence: 96%
“…Nowadays it is crucial for the aquafeed industry to optimise the use of dietary protein and to improve protein utilisation in fish feeds. The protein sparing effect has been shown in several studies on common carp (Steffens, 1996;Cho et al, 2001), but an excessive fat accumulation in the fish carcass was observed (Keshavanath et al, 2002). Several studies have examined the replacement of FO with RO or other VO in the diets of cyprinids (Steffens et al, 1995;Pozernick and Wiegand, 1997;Du et al, 2008;Zakęś et al, 2010), and also the use of low protein/high carbohydrates diets (Cho et al, 2001;Khan et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation